Hand and Wrist Trauma: Antimicrobials and Infection (HAWAII): a protocol for a multicentre, feasibility study of antimicrobial sutures in hand and wrist trauma surgery. (1st July 2022) - Wormald, Justin C. R.; Rodrigues, Jeremy N.; Cook, Jonathan A.; Prieto-Alhambra, Daniel; Costa, Matthew L.
Abstract : Aims: Hand trauma accounts for one in five of emergency department attendances, with a UK incidence of over five million injuries/year and 250, 000 operations/year. Surgical site infection (SSI) in hand trauma surgery leads to further interventions, poor outcomes, and prolonged recovery, but has been poorly researched. Antimicrobial sutures have been recognized by both the World Health Organization and the National Institute for Clinical Excellence as potentially effective for reducing SSI. They have never been studied in hand trauma surgery: a completely different patient group and clinical pathway to previous randomized clinical trials (RCTs) of these sutures. Antimicrobial sutures are expensive, and further research in hand trauma is warranted before they become standard of care. The aim of this protocol is to conduct a feasibility study of antimicrobial sutures in patients undergoing hand trauma surgery to establish acceptability, compliance, and retention for a definitive trial. Methods: A two-arm, multicentre feasibility RCT of 116 adult participants with hand and wrist injuries, randomized to either antimicrobial sutures or standard sutures. Study participants and outcome assessors will be blinded to treatment allocation. Outcome measures will be recorded at baseline (preoperatively), 30 days, 90 days, and six months, and will include SSI, patient-reported outcome measures, and return to work. Conclusion: This will inform a definitive trial of antimicrobial sutures in the hand and wrist, and will help to inform future upper limb trauma trials. The results of this research will be shared with the medical community through high impact publication and presentation. Cite this article: Bone Jt Open  2022;3(7):529–535.